An investigation of thermal behaviour of biomass and coal during copyrolysis using thermogravimetric analysis. (7th October 2013) - Vhathvarothai, Navirin; Ness, James; Yu, Qiming J.
SUMMARY The biomass, coal and their blends at blending ratios (biomass : coal) of 95:5, 90:10, 85:15 and 80:20 were pyrolysed under a nitrogen environment at four different heating rates comprising 5°C, 10°C, 15°C and 20°C per minute to investigate their pyrolytic behaviour and to determine kinetic parameters of thermal decomposition through Kissinger's corrected kinetic equation using the thermogravimetric analysis results. In the kinetic analysis, the activation energy of both types of biomass was less than that of coal, being 168.7 kJ/mol (cypress wood chips), 164.6 kJ/mol (macadamia nut shells) and 199.6 kJ/mol (Australian bituminous coal). The activation energy of the blends of biomass and coal followed that of the weighted average of the individual samples in the blends. Char production of the samples and the blends was also analysed to observe any synergetic effects and thermal interaction between biomass and coal. The char production of the blends corresponded to the sum of the results for the individual samples with the coefficient of determination of 0.999. Thermal decomposition of biomass and coal appeared to take place independently, and thus, the activation energy of the blends can be calculated from that of the two components. There was no evidence for any significant synergetic effects and thermal interaction between either type of biomass and coal during copyrolysis. Copyright © 2013 John Wiley & Sons, Ltd.